Improving The Learners' Writing Skill Through Dictogloss(A Classroom Action Research at Grade IX I of SMP Negeri 3Ungaran in the Academic Year 2011-2012) - Sugiarti, Sugiarti (2012)
During the last two semesters, the learners' writing scores were below the passing grade. The scores of their writing pretest are low as well which indicates their low writing skill. That's why the condition needs improvement. Therefore, this study is aimed at: 1. Improving the learners' writing skill through dictogloss at grade IX I of SMP Negeri 3 Ungaran, and 2. Explaining the effectiveness of the learners' learning when dictogloss is implemented in the teaching of writing. The effectiveness can be observed through the learners' characteristics as effective learners in the writing classroom. The research setting is at SMP Negeri 3 Ungaran. The data sources are the learners' writing scores in pretest and post-tests, informants, as well as the learners' in the writing classroom. The qualitative data which are collected through observation, interview and questionnaires are analyzed with constant comparative method. The quantitative data obtained through pretest and pos-tests are analyzed with statistic descriptive. The data are validated through triangulation method. There are four indicators as a reference of the success of dictogloss implementation to improve the learners' writing skill: (1) The improvement of the learners' writing scores; (2) The increase of the standard category; (3) The mean of each writing component achieve or exceed the passing grade; and (4) The learners are more active, participative and creative than before. Finally, this study shows that dictogloss can improve the learners' writing skill as indicated by the improvement of their writing scores as well as their motivation in writing as indicated by the better changes of their behavior in the writing classroom. The learners' scores increase from the level of fair (the mean = 54.14) in pretest to the level of very good (the mean = 80.57) in the post-test of cycle 3. The learners' learning is also effective when dictogloss is implemented in the teaching of writing.